2018
DOI: 10.1080/02713683.2018.1501802
|View full text |Cite
|
Sign up to set email alerts
|

Optical Performance of the Cornea One Year Following Keratoconus Treatment with Corneal Collagen Cross-Linking

Abstract: CXL treatment for keratoconus led to an improvement in visual, refractive, topographic, and most corneal HOAs outcomes at the 12-month follow-up. However, these improvements were not enough to increase corneal MTF and the Strehl ratio of PSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…27 The biomechanical implication of the DL depth can be explained by considering that ectasia originates in almost all cases from the posterior float of the cornea. 86 The well-known structure of the human corneal stromal has been revealed by many studies based on X ray diffraction [87][88][89][90][91] . The anisotropy, the orientation, the intersection and the distribution of corneal lamellar structure and collagen fibrils interweaves are not uniform across the thickness of the stroma, but the reinforcing structure characterizes a stronger cornea in the anterior third (160-180µm) and a progressively weaker stroma in the posterior part (over 160-180).…”
Section: Discussionmentioning
confidence: 99%
“…27 The biomechanical implication of the DL depth can be explained by considering that ectasia originates in almost all cases from the posterior float of the cornea. 86 The well-known structure of the human corneal stromal has been revealed by many studies based on X ray diffraction [87][88][89][90][91] . The anisotropy, the orientation, the intersection and the distribution of corneal lamellar structure and collagen fibrils interweaves are not uniform across the thickness of the stroma, but the reinforcing structure characterizes a stronger cornea in the anterior third (160-180µm) and a progressively weaker stroma in the posterior part (over 160-180).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, different degrees of improvement in K max were recorded within a one-year follow-up after CXL. Uysal et al [25] reported that 109 eyes had a stable K max (45.9%) or a decreased K max up to 3.0 D (52.2%) one year after CXL treatment based on a retrospective study with 111 eyes recruited. Kumar et al [26] reported that the preoperative K max was 55.11 D (SD±5.34), whereas the mean of postoperative K max was reduced to 53.87 D (SD±4.99) based on their retrospective study recruiting 34 eyes.…”
Section: Discussionmentioning
confidence: 99%
“…MTF reveals the degree of detail preservation in the image of the object in various spatial frequencies and serves as a measure of ocular contrast sensitivity. Sharper retinal images show less light deviation from the optical system, and PSF represents the retinal image from a light source [ 12 14 ]. There are several studies report the results of each technique individually, but there are limited studies that compared these two techniques regarding visual outcome, corneal biomechanics, specular microscopy, keratometry, contrast sensitivity and high order aberrations.…”
Section: Introductionmentioning
confidence: 99%